Accompaniment students' formative trajectory, in a context of curriculum innovation (LACCEI, 2024)
In 2014, the Faculty of Engineering and Sciences (FICA) of the Universidad de la Frontera (UFRO), together with the Faculties of Engineering of the Chilean universities of Bio-Bio and Talca, were awarded the contest "Implementation of the strategic plan - new engineering for 2030", a project whose main purpose was to "train world-class engineers", by incorporating in its educational process the international quality standards identified for the discipline, as well as its advances. The Chilean State, through the Production Development Corporation (CORFO) financed these initiatives, in which curricular innovation processes were promoted in the different engineering careers of these higher education institutions, under a process of harmonization understood as the degree of convergence, homologation and/or compatibility between the different elements that make up the training plans. Thus, in the year 2021, in the midst of the pandemic, and after many years of reflection and curricular construction, the Board of Directors of the UFRO approved the curricular innovation of the twelve civil engineering careers taught at this university, among the approved changes are: New degree profiles, Redesign of the basic cycle, incorporation of the bimester (academic period of 8 weeks duration) in the mathematics subjects of the first year, incorporation of pedagogical and psychological elements of accompaniment to the students, through an articulated work with internal instances of the university. Readjustment of degree mechanisms, and design of an integrative line of educatión in engineering and science to develop design, social responsibility and innovation competencies, applying STEM methodologies. As can be seen, it is a complex process of curricular innovation, which will begin to be implemented in 2022 under pandemic scenarios, product of COVID-19, which has affected the profile of students' entry to higher education, which is why it was necessary to analyze this context and the challenges that these curricula bring with them, This is the reason why we had to analyze this context and the challenges that these curricula bring with them, in order to look for options to implement the new curricular designs in the best possible way, providing all the necessary help to the main actors of the formative process, the students, to achieve success in their university studies, thus creating the System of accompaniment of the student's formative trajectory.